Methaemoglobinaemia in pregnancy with chronic kidney disease an uncommon case: a case report - Gok, Mahmut; Yasemin Gul Aydemir (Journal of the Pakistan Medical Association, 2022)
The development of methaemoglobinaemia due to prilocaine, which is used for local anaesthesia, is a rare, life-threatening, but well-known side effect. The development of this side-effect in a pregnant patient with chronic kidney disease can lead to foetal distress. The case presented here is of a 21-year old pregnant female with chronic kidney disease who required haemodialysis in the 22nd week of pregnancy due to the progression to end-stage kidney disease. During haemodialysis, a right jugular tunneled double-lumen catheter was inserted using prilocaine as the local anaesthetic. Prilocaine-induced methaemoglobinaemia was diagnosed. In the 24-hour follow-up, the methaemoglobin level decreased to normal with oxygen supply of 10-15 L/min, 2 units of erythrocyte suspension and accompanying haemodialysis. Keywords: Methemoglobinemia, prilocaine, pregnancy, hemodialysis Continuous...